Revisiting a Criminological Classic: the Cycle of Violence - Myers, Wesley (Journal of contemporary criminal justice, 2018)
There is a growing “replication crisis” in the social and behavioral sciences, where original research across a wide array of substantive areas has failed to replicate when conducted by others. This problem highlights the importance of carefully revisiting original research—particularly studies that have exerted a significant influence over the field. Accordingly, in the present study, we subject Widom’s classic work, “The Cycle of Violence,” to a rigorous empirical reproduction and extension. We subjected her original data to alternative analytic techniques and to different measurement strategies and model specifications. Our results indicated that although we were able to replicate her original results, the link between childhood physical abuse and violence in adulthood failed to survive the robustness checks we conducted. Instead, childhood neglect emerged as the most robust predictor of adult violence.